Caregiver assessment of quality of life in individuals with genetic developmental and epileptic encephalopathies. (28th February 2022) - Cohen, Stacey R.; Helbig, Ingo; Kaufman, Michael C.; Schust Myers, Leah; Conway, Laura; Helbig, Katherine L.
Abstract : Aim: To summarize quality of life (QoL) and its determinants, including disease severity, in individuals with developmental and epileptic encephalopathies (DEEs) through a tailored questionnaire. Method: A questionnaire containing 89 items addressing demographic characteristics, genetic diagnosis, clinical features, and QoL was distributed to primary caregivers of individuals with DEEs through patient advocacy organizations. Composite scores were generated from the mean values of QoL items, grouped into domain scores. Results: Out of 176 received responses, the most common genetic diagnoses reported were SCN2A ( n =42/173, 24%), SLC6A1 ( n =28/173, 16%), SCN1A ( n =22/173, 13%), and KCNQ2 ( n =21/173, 12%). Composite QoL scores centered around a mean score of 61.67 of 100 (SD 17.10). QoL scores were strongly associated with the number of days minimally disrupted by seizures, medication side effects, genetic diagnosis, and community type. The mean QoL scores for individuals with DEEs was significantly lower than for individuals with Rett syndrome, cerebral palsy, autism spectrum disorder, and Down syndrome. Interpretation: QoL in DEEs can be assessed through a standardized instrument. QoL only partially overlaps with objective measurements of disease severity and may represent an independent outcome measure in precision medicine trials. Abstract : This survey‐based, cross‐sectional study characterizes disease burden, quality‐of‐life, and the relationship between the two, in children with genetic developmental and epileptic encephalopathies.